Termination of a Trench-Linked Strike-Slip Fault Zone in the Sumatra–Java Forearc Basin and Accretionary Wedge Complex - Maruf M Mukti; Ilham Arisbaya; Haryadi Permana (Pusat Survei Geologi, 2020)
This paper presents a review of several published seismic reflection and seismicity data and analyzes of high-resolution bathymetry data to revise the exact location and reveal detail characteristics of a strike-slip fault zone that formed the southernmost segment of the Sumatran Fault (SF). Previous works interpreted this fault segment as a horst structure to the south of a pull-apart basin. We observe a clear linear trace of dissected seafloor parallels to SF in the high-resolution bathymetric map. This structure extends from the south of a pull-apart basin in the northwest to the Sunda accretionary wedge farther southeast. This lineament exhibits a narrow valley and a linear ridge that in the subsurface are interpreted as negative and positive flower structures, respectively. The structure exhibits a vertical fault plane and appears to have deformed the accretionary wedge sediments and basement at depth. A cluster of shallow seismicity is observed along this NW-trending fault zone, indicating the activity of this zone. Here, we proposed this strike-slip fault as the Ujung Kulon Fault that marks the southeasternmost segment of the SF zone. This segment deformed the area of the Sumatra-Java forearc basin and terminated in accretionary wedge near the trench. The accumulated strain within UKF may trigger large earthquake in the future, close to the highly populated areas in the coast of Sumatra and Java.Keywords: Strike-slip fault, Sumatra Fault, Ujung Kulon Fault, segmentation, earthquake.